If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 47 = 180 Reorder the terms: 47 + 3x = 180 Solving 47 + 3x = 180 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-47' to each side of the equation. 47 + -47 + 3x = 180 + -47 Combine like terms: 47 + -47 = 0 0 + 3x = 180 + -47 3x = 180 + -47 Combine like terms: 180 + -47 = 133 3x = 133 Divide each side by '3'. x = 44.33333333 Simplifying x = 44.33333333
| 12.25-.75=x | | 4+(a/5)=2 | | 1+6=3+2x | | -3(3y-4)-y=-2(y-4) | | 1-9/6x=2/5 | | 1+3y=5/3y | | (3x-1)/4=-5/11 | | 2/3(6y+9)=20 | | 4(x-1)-2(3x+5)=3x-1 | | a+2b=50 | | 5x=3/7 | | 5x^3=3x^2 | | 12+3p=2p+4 | | 2x=3y-10 | | A=5k/7y | | 12x-8=-20 | | 3x+5=9y-4+z | | a+a+7=3+a | | 3[4(3x+1)-(10x-9)]=7x+9 | | x=2y^2-4 | | (2x-3)/4=(3-2x)/6 | | 2x-(1/x)=1 | | x^2-x-x=0 | | 2X+7X-12=33 | | X^2-2x-12=-12 | | 7(t-6)+7t=7(2t+3)-10 | | -6=(y-4)/9 | | 1/2(4y+3)=1/4(y+8) | | 7y+12/t=36 | | 61=6x-11 | | 3(2x+1)+13x-12=18x-3 | | -1=x/3-7 |